The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2053369118824920
|View full text |Cite
|
Sign up to set email alerts
|

British Menopause Society consensus statement on the management of estrogen deficiency symptoms, arthralgia and menopause diagnosis in women treated for early breast cancer

Abstract: This guidance document by the British Menopause Society provides an overview of the management of women experiencing estrogen deficiency symptoms and arthralgia following a breast cancer diagnosis. It is now recommended that breast cancer patients are referred to health care professionals with an expertise in menopause for the management of such symptoms, which in turn often involves liaison with patients' breast cancer teams. However, as many women initially present to primary health care professionals for ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 82 publications
0
4
0
1
Order By: Relevance
“…В качестве 1-й линии терапии менопаузальных расстройств у женщин с эстрогензависимыми онкологическими заболеваниями органов репродуктивной системы используются негормональные фармакологические и нефармакологические методы коррекции [43].…”
Section: лечение менопаузальных симптомовunclassified
“…В качестве 1-й линии терапии менопаузальных расстройств у женщин с эстрогензависимыми онкологическими заболеваниями органов репродуктивной системы используются негормональные фармакологические и нефармакологические методы коррекции [43].…”
Section: лечение менопаузальных симптомовunclassified
“…10,11 Vaginal hormonal estrogen remains the first-line hormonal therapy in the United Kingdom for breast cancer survivors experiencing genitourinary symptoms of menopause. 12, 13 Studies have shown that vaginal estrogen effectively relieves the GSM and significantly improves vaginal mucosal health and vaginal pH in postmenopausal women. 5 Furthermore in healthy postmenopausal women, the Women's Health Initiative observational study determined that the risk of breast cancer was not increased following the use of vaginal estrogens.…”
Section: Introductionmentioning
confidence: 99%
“…The broad literature on menopause (outside of MOS) mostly adopts a biomedical lens where menopause (and by extension menopausal women) is akin to disease and deficiency (Atkinson, Beck et al., 2021). For example, menopause is defined as ovarian dysfunction (Perlman et al., 2018) or estrogenic deficiency (Marsden et al., 2019). It is almost always framed as something that needs to be managed, cured, and relieved (Krajewski, 2019).…”
Section: Introductionmentioning
confidence: 99%